Wide Excision of a Retroperitoneal Liposarcoma with En Bloc Ureterectomy and Renal Salvage by Autotransplantation - Siegfredo R. Paloyo; Arjel D. Ramirez; Ferri P. David-Paloyo; Rodney B. Dofitas (Case Reports in Transplantation)
Liposarcoma is a malignant mesenchymal neoplasm composed of adipose tissue with varying degrees of atypia. These tumors grow slowly and may reach an enormous size particularly if located in the retroperitoneum. We report a 40-year-old male with a 6-month history of gradual abdominal enlargement. Computed tomography (CT) of the abdomen showed a huge retroperitoneal mass with characteristic features consistent with liposarcoma. On laparotomy, the mass was noted to be encasing the right ureter for which a wide excision with en bloc ureterectomy and subsequent renal autotransplantation for organ preservation was done. Post-operative course was uneventful with excellent outcome after 6 months of follow-up. Final histopathologic diagnosis was low-grade, well differentiated liposarcoma, which has favorable prognosis following radical surgery. This was the first report of such a case in the Philippines.